Aroma encapsulation and aroma delivery by oil body suspensions derived from sunflower seeds (Helianthus annus) - Fisk, Ian D.; Linforth, Rob S.T.; Taylor, Andrew J.; Gray, David A. (Springer Berlin / Heidelberg, 2011)
Oil bodies are small discrete cell organelles that can be found within oilseeds. Oil bodies have been investigated previously as a potential technology platform for use within the food industry, offering stable, antioxidant-enriched lipid-delivery systems. In this study, the use of oil bodies as a flavour delivery agent is evaluated. Fresh aromatized oil bodies show comparable headspace flavour intensity to phospholipid-stabilized emulsions when in a static equilibrium state, and when evaluated by dynamic headspace dilution, aromatized oil bodies showed a significantly stronger potential to maintain their headspace volatile concentration, which may indicate that oil bodies would offer greater retronasal flavour delivery than current commercial systems.